The value of indigenous knowledge for enhancing smallholders’ resilience to climate change and food insecurity: a case study of small-scale irrigation system in Niger - Abdoulkarim Issoufou Kalidou; Gubo Qi; Gabriel Kanuti Ndimbo; Bin Wu (International Journal of Agricultural Sustainability)
The global south faces challenges in enhancing smallholder farmers' resilience to climate change and food insecurity. Indigenous knowledge and small-scale irrigation (SSI) systems are being promoted as a viable solution to address these challenges. This paper explores how smallholder farmers use local knowledge to establish informal and farmer-led SSI to enhance smallholders' resilience in agriculture and livelihoods. A qualitative research approach with 79 semi-structured interviews was carried out with farmers' households in Tamaske rural community in Southwest Niger, followed by thematic and statistical analysis. The results revealed that an alternative SSI strategy is mostly based on internal agencies rather than externally supported and it serves as a tool to enhance household food and income security amid climate change. The empirical case allows us to assess the value of indigenous knowledge in agriculture by asking how local people can bring together ideas and resources to enhance SSI and build resilience to climate change. The study suggests that the initiation and multiplication of SSI systems can be achieved by farmers' own agencies if appropriate technology and cooperation mechanisms are selected. The policy focus should promote simple, root-based technology as limited government financial support in the global south may hinder this progress.